2021
DOI: 10.1111/1346-8138.15782
|View full text |Cite
|
Sign up to set email alerts
|

Invasive and in situ lesions of squamous cell carcinoma are independent factors for postoperative surgical‐site infection after outpatient skin tumors surgery: A retrospective study of 512 patients

Abstract: Surgical-site infection (SSI) is one of the major postoperative complications in surgery. Although the rate of SSI in dermatological surgery is regarded as low, it may cause significant morbidity such as ruptured suture or skin necrosis. 1 Dermatological surgeries for skin tumors involve various tumor types, surgical methods, and surgical sites, and these factors differ in each case. However, factors associated with SSI in dermatological surgery are not fully elucidated.Moreover, there are currently no standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
42
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(45 citation statements)
references
References 9 publications
(25 reference statements)
1
42
0
2
Order By: Relevance
“…Meta-analysis of 4 studies showed a tendency toward a higher risk for SSI below the knee. 11–14 The finding was not significant, and heterogeneity was substantial (RR 2.81, CI 0.91–8.68, I 2 = 86%, see Supplemental Digital Content , Figure S9, http://links.lww.com/DSS/B4). In line with the analysis of the lower extremity, this may be due to differences in the surgical setting: By contrast to the remaining studies, the only study which showed no risk difference included hospitalized patients.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Meta-analysis of 4 studies showed a tendency toward a higher risk for SSI below the knee. 11–14 The finding was not significant, and heterogeneity was substantial (RR 2.81, CI 0.91–8.68, I 2 = 86%, see Supplemental Digital Content , Figure S9, http://links.lww.com/DSS/B4). In line with the analysis of the lower extremity, this may be due to differences in the surgical setting: By contrast to the remaining studies, the only study which showed no risk difference included hospitalized patients.…”
Section: Resultsmentioning
confidence: 99%
“…Meta-analysis of 7 studies showed no risk difference for SSI on the upper extremity (RR 1.66 CI 0.63-4.37, I 2 5 75%, see Supplemental Digital Content, Figure S9, http:// links.lww.com/DSS/B4). 7,[11][12][13][17][18][19] Heterogeneity among the studies was substantial, and the direction of the effect varied. Five studies were retrospective and 2 prospective.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations